2017
DOI: 10.1037/xhp0000375
|View full text |Cite
|
Sign up to set email alerts
|

The role of error processing in the contextual interference effect during the training of perceptual-cognitive skills.

Abstract: The contextual interference (CI) effect refers to the learning benefits that occur from a random compared with blocked practice order. In this article, the cognitive effort explanation for the CI effect was examined by investigating the role of error processing. In 2 experiments, a perceptual-cognitive task was used in which participants anticipated 3 different tennis skills across a pretest, 3 practice sessions, and retention test. During practice, the skills were presented in either a random or blocked pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…Recent research indicates that frequent error processing in addition to task switching increases cognitive effort and may encourage implicit learning (Broadbent et al, 2017). In both experiments presented here we found that those in the interleaved condition were less accurate than those in the blocked condition on Day 1, which may lend some credence to the theory that frequent error processing may occur with high CI (Broadbent et al, 2017).…”
Section: Summary and Concluding Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Recent research indicates that frequent error processing in addition to task switching increases cognitive effort and may encourage implicit learning (Broadbent et al, 2017). In both experiments presented here we found that those in the interleaved condition were less accurate than those in the blocked condition on Day 1, which may lend some credence to the theory that frequent error processing may occur with high CI (Broadbent et al, 2017).…”
Section: Summary and Concluding Discussionsupporting
confidence: 81%
“…Previous research showing increased levels of cognitive activity with interleaved practice as compared to blocked practice lends some support to this theory (Li & Wright, 2000). Recent findings extend this idea, suggesting that high cognitive effort seen in interleaved practice may be partially due to increased error processing as well as task-switching (Broadbent et al, 2017). Following an error, greater cognitive activity could be attributed to an individual updating and correcting a rule as well as retrieving information for the upcoming task.…”
Section: Theorized Mechanisms Of the Contextual Interference Effectmentioning
confidence: 74%
See 1 more Smart Citation
“…Deliberate introduction of contextual interference decreases performance during motor skill acquisition and improves later retention [ 11 ]; however, too much contextual interference reduces retention performance [ 12 ], indicating that some degree of contextual interference is desirable, while too much is undesirable. Two theories have been developed to explain contextual interference effects: elaborative processing and action plan reconstruction [ 13 14 ]. Elaborative processing is based on changes in the number of inter- and intra-task comparisons, which can be manipulated by deliberately introducing additional tasks in working memory, such as through frequent task changes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elaborative processing is based on changes in the number of inter- and intra-task comparisons, which can be manipulated by deliberately introducing additional tasks in working memory, such as through frequent task changes [ 15 ]. Action plan reconstruction is activated when a motor skill has left working memory, which requires recall of the action plan from long-term memory before the action can be performed [ 14 ]. A contextual interference theory that combines neural and behavioral data suggests a role for both elaboration and reconstruction processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%